Abraham Lincoln, Esq. : the legal career of America's greatest president - Billings, Roger D.; Williams, Frank J. (University Press of Kentucky, 2010)
As our nation's most beloved and recognizable president, Abraham Lincoln is best known for the Emancipation Proclamation and for guiding our country through the Civil War. But before he took the oath of office, Lincoln practiced law for nearly twenty-five years in the Illinois courts. Abraham Lincoln, Esq.: The Legal Career of America's Greatest President examines Lincoln's law practice and the effect it had on his presidency and the country.